Risk of pre-eclampsia after fresh or frozen embryo transfer in patients undergoing oocyte donation. (August 2018) - Blazquez, Anna; García, Désirée; Vassena, Rita; Figueras, Francesc; Rodriguez, Amelia
Abstract: Objectives: Different perinatal and neonatal adverse outcomes have been reported to be increased in frozen embryo transfer pregnancies compared with fresh embryo transfer with patient's own oocytes. Concerning preeclampsia, it has also been reported to be increased after frozen embryo transfer. The objective of this study is to asses if there is an increased risk of preeclampsia and gestational hypertension in pregnancies achieved with oocyte donation after frozen embryo transfer compared to fresh embryo transfer. Study design: Retrospective cohort study of 433 patients who underwent a cycle with donated oocytes either after fresh (n = 353) or frozen embryo transfer (n = 80) between March 2013 and April 2016 at a large fertility clinic. Participants are pregnant patients who reached the 20th week of gestation. The risk of preterm preeclampsia (presenting before 37 weeks of gestation), term preeclampsia (presenting at or after 37 weeks of gestation) and gestational hypertension are presented as unadjusted and adjusted odds ratio (OR). Results: Frozen embryo transfer have similar risk for developing preterm preeclampsia compared to fresh embryo transfer, with an OR of 1.95 (CI 95% 0.72, 5.26, p = 0.18), as well as term preeclampsia (OR 0.3, 95%CI 0.04, 2.35, p = 0.25), and gestational hypertension (OR 1.45, 95% CI 0.75, 2.81, P = 0.27). Conclusions: Despite a high prevalence of preeclampsia in pregnancies achieved by oocyte donation, the freezing-thawing process does not confer more risk than the fresh embryo transfers in preterm preeclampsia, term preeclampsia or gestational hypertension.